Epoxy-Glass Microballoon Syntactic Foams: Rheological Optimization of the Processing Window - A. V. Ullas; Devendra Kumar; Prasun Kumar Roy (Advances in Polymer Technology)
In this paper, we discuss the chemorheology of epoxy based syntactic foams containing glass microballoons of varying density, with an aim of establishing the effect of microballoon loading on its processability. The primary objective is to determine the maximum microballoon loading that disperses uniformly in the resin without the aid of any diluent. The viscosity and dynamic mechanical properties of epoxy formulations containing varying amounts of glass microballoons were established by parallel plate rheometry. Our studies reveal that solventless processing of formulations with microballoon loading > 60% poses practical difficulties due to prohibitively high viscosities, although a packing efficiency of 74% is theoretically allowed in the case of hexagonal close packing. The presence of microballoons does not alter the curing mechanism. The mechanical properties of syntactic foams were inversely proportional to the loading and type of glass microballoons.